Ultrarobust subzero healable materials enabled by polyphenol nano-assemblies - Wang, Nan; Yang, Xin; Zhang, Xinxing (Nature communications, 2023)
Bio-inspired self-healing materials hold great promise for applications in wearable electronics, artificial muscles and soft robots, etc. However, self-healing at subzero temperatures remains a great challenge because the reconstruction of interactions will experience resistance of the frozen segments. Here, we present an ultrarobust subzero healable glassy polymer by incorporating polyphenol nano-assemblies with a large number of end groups into polymerizable deep eutectic solvent elastomers. The combination of multiple dynamic bonds and rapid secondary relaxations with low activation energy barrier provides a promising method to overcome the limited self-healing ability of glassy polymers, which can rarely be achieved by conventional dynamic cross-linking. The resulted material exhibits remarkably improved adhesion force at low temperature (promotes 30 times), excellent mechanical properties (30.6 MPa) and desired subzero healing efficiencies (85.7% at −20 °C). We further demonstrated that the material also possesses reliable cryogenic strain-sensing and functional-healing ability. This work provides a viable approach to fabricate ultrarobust subzero healable glassy polymers that are applicable for winter sports wearable devices, subzero temperature-suitable robots and artificial muscles. Self-healing materials hold great promise for applications in wearable electronics, artificial muscles and soft robots but selfhealing at subzero temperatures remains a great challenge. Here, the authors present a robust subzero healable glassy polymer by incorporating polyphenol nano-assemblies with a large number of end groups into polymerizable deep eutectic solvent elastomers.